PENGARUH AKTIFITAS GALERI INVESTASI, MODAL MINIMAL INVESTASI, PERSEPSI RESIKO DAN PERSEPSI RETURN TERHADAP MINAT INVESTASI SAHAM SYARIAH (Studi pada Mahasiswa Uniska MAB Banjarmasin) - Purboyo; Rizka Zulfikar; Teguh Wicaksono (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
Stocks traded on the Indonesia Stock Exchange (IDX) in addition to conventional stocks also have sharia shares, sharia shares are shares traded on the capital market and do not conflict with Islamic law, the purpose of this study is to know and analyze the effects of investment gallery activities, Minimum investment capital, risk perceptions and perceptions of return in sharia investments among Uniska MAB Banjarmasin students. The population in this study were Uniska MAB Banjarmasin students with a sample of 137 respondents. Sampling using a purposive sampling method, and the number of samples based on Slovin formula. Data collection uses a questionnaire, then do data editing. Data analysis techniques using SEM (Structural Equation Model) analysis using IBM AMOS version 22 software, so that the model that will explain the relationship between variables to explain the interest in investing in sharia stocks. The results of this study are: (1) The variable of investment gallery activities have a significant effect on students' interest in investing in Islamic stocks. (2) Perception of return does not have a significant effect on the interest of students to invest in Islamic stocks. (3) Risk perception has no significant effect on the interest of students to invest in sharia. (4) Minimum investment capital has a significant effect on students' interest in investing in sharia.